Om possessiva adjektiv i polskan och svenskan - Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2016)
The article discusses possessive adjectives in Polish (derived from nouns and used to mark possession), their structure and functional scope as well as diachrony, and contrasts them with similar formations in Swedish. Adjectives derived from names and surnames are a marginal phenomenon in the Scandinavian languages and as such absent from most grammatical descriptions; their scope of use is limited. However, a comparison with Polish allows a new perspective on these adjectives in Polish as an alternative possessiva structure. The analysis is based on corpora search of Polish and Swedish texts.